Development of a low-seroprevalence, αvβ6 integrin-selective virotherapy based on human adenovirus type 10 - Bates, Emily A; Davies, James A; Váňová, Jana; Nestić, Davor; Meniel, Valerie S; Koushyar, Sarah; Cunliffe, Tabitha G; Mundy, Rosie M; Moses, Elise; Uusi-Kerttula, Hanni K; Baker, Alexander T; Cole, David K; et al. (Molecular therapy oncolytics, 2022)
Oncolytic virotherapies (OV) hold immense clinical potential. OV based on human adenoviruses (HAdV) derived from HAdV with naturally low rates of pre-existing immunity will be beneficial for future clinical translation. We generated a low-seroprevalence HAdV-D10 serotype vector incorporating an αvβ6 integrin-selective peptide, A20, to target αvβ6-positive tumor cell types. HAdV-D10 has limited natural tropism. Structural and biological studies of HAdV-D10 knob protein highlighted low-affinity engagement with native adenoviral receptors CAR and sialic acid. HAdV-D10 fails to engage blood coagulation factor X, potentially eliminating "off-target" hepatic sequestration in vivo. We engineered an A20 peptide that selectively binds αvβ6 integrin into the DG loop of HAdV-D10 fiber knob. Assays in αvβ6+ cancer cell lines demonstrated significantly increased transduction mediated by αvβ6-targeted variants compared with controls, confirmed microscopically. HAdV-D10.A20 resisted neutralization by neutralizing HAdV-C5 sera. Systemic delivery of HAdV-D10.A20 resulted in significantly increased GFP expression in BT20 tumors. Replication-competent HAdV-D10.A20 demonstrated αvβ6 integrin-selective cell killing in vitro and in vivo. HAdV-D10 possesses characteristics of a promising virotherapy, combining low seroprevalence, weak receptor interactions, and reduced off-target uptake. Incorporation of an αvβ6 integrin-selective peptide resulted in HAdV-D10.A20, with significant potential for clinical translation.
Keywords: structure; oncolytic; virotherapy; targeting; low seroprevalence; adenovirus; αvβ6 integrin